Development of a transformer courseware using Scala MM200 - Aris, Ishak; Lai, Kwang Fatt (2000)
Transformer is one of the important topics in an electrical engineering course. It is widely used in power engineering applications. Since it is widely used and important to power engineering applications therefore a topic on the transformer is included in the electrical engineering course at universities. Engineering students always have problems of understanding and digesting their engineering courses. Understanding by reading texts can be time consuming, hard and sometimes boring. This paper deals with the development of a transformer courseware using a multimedia technique. The development of this multimedia courseware is not a substitute for the regular studying method, but it is rather an additional studying tool for students and an additional teaching tool for teachers or lecturers. The courseware was developed using integration of software such as Scala MM200, Adobe PhotoShop5, 3D Eureka and Ulead Cool 3D, Animator SoundLab and Animator Studio. In its development stage, the text, data, graphic, voice, sound, music and animation are combined together into a single synchronise production to make students understand the transformer topic easily. The multimedia courseware, which is published into a CD-ROM, can be accessed easily through any personal computers. In the courseware, it contains four main sections. They include applications, theories, quizzes and lists of reference books on the transformer. The first section, which is the applications of transformer, explains the basic applications of transformer in industries and its classification. The second section, which is the theories on the transformer, provides ten basic topics about the transformer. The third section, which is the quiz on the transformer, provides some multiple choices questions for the students to test themselves after reading its theories section. The last section, which is the list of reference books on the transformer, allows the students to look for more information on the transformer. By using this multimedia courseware, the student’s learning process will become more effective, attractive and interesting.